Development of an Exoskeleton-Type Assist Suit Utilizing Variable Stiffness Control Devices Based on Human Joint Characteristics - Seigo Kimura; Ryuji Suzuki; Katsuki Machida; Masashi Kashima; Manabu Okui; Rie Nishihama; Taro Nakamura (Actuators, 2021)
In this paper, the prototype of the assistive suit for lower limbs was developed. The prototype was based on an assist method with joint stiffness and antagonized angle control. The assist method comprises a system consisting of a pneumatic artificial muscle and a pull spring, which changes the joint stiffness and the antagonized angle to correspond to the movement phase and aims at coordinated motion assistance with the wearer. First, the characteristics of the developed prototype were tested. It was confirmed that the measured value of the prototype followed the target value in the relationship between torque and angle. In addition, there was hysteresis in the measured value, but it did not affect the assist. Next, the evaluation of standing-up and gait assist by measuring electromyography (EMG) of the knee extensor muscle was conducted using the prototype. In all subjects, a decrease in EMG due to the assist was confirmed. In one subject, the maximum decrease rate at the peak of the EMG was about 50% for standing-up motion and about 75% for gait motion. From the results of these assist evaluations, the effectiveness of the assist method based on the joint stiffness and antagonistic angle control using the prototype was confirmed.